2002
DOI: 10.1053/jopr.2002.127619
|View full text |Cite
|
Sign up to set email alerts
|

Retention strengths of five luting cements on prefabricated dowels after root canal obturation with a zinc oxide/eugenol sealer: 1. Dowel space preparation/cementation at one week after obturation

Abstract: Paraposts cemented with Panavia 21 in unobturated root canals exhibited significantly higher retention than Paraposts luted with Panavia 21 and 4 different cements into dowel spaces prepared 1 week after obturation with gutta percha/ZOE sealer (p <0.001). Among the obturated groups, Panavia 21 cement (group 2) demonstrated significantly greater retention of Paraposts than zinc phosphate (group 4) and Parapost composite (group 5) cements (p <0.001). Ketac-Cem glass ionomer cement (group 3) had intermediate rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 16 publications
2
18
1
1
Order By: Relevance
“…The present study showed that the highest bond strength was in the control group in which no canal sealer was used (p < 0.001), which agreed with several other studies (18,29). The present study's result was most probably attributable to the open dentin tubule orifices allowing maximum penetration of resin cement after the application of acidic monomer (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study showed that the highest bond strength was in the control group in which no canal sealer was used (p < 0.001), which agreed with several other studies (18,29). The present study's result was most probably attributable to the open dentin tubule orifices allowing maximum penetration of resin cement after the application of acidic monomer (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Most studies have determined that eugenol-based sealers decrease the bond strength of resinous cement (18,19,32,33). In the present study, the eugenol-based sealer group had the lowest bond strength (Table 1), but no significant difference was found between the eugenol and resin-based sealer groups (p > 0.05).…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…However, it is unclear if the presence of eugenol impairs post retention. Some authors performing different methodologies found a reduction in the retentive capacity of posts cemented after the use of a eugenol-based sealer (11,(17)(18)(19)(20)(21), whereas others did not observe this change (22)(23)(24)(25). Thus, the aim of this study was to systematically review the literature and perform meta-analysis on the influence of eugenol on the bond strength of posts luted to root canals evaluated by the push-out test.…”
mentioning
confidence: 96%